2011
DOI: 10.1002/cne.22546
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar cells of the ground squirrel retina

Abstract: Parallel processing of an image projected onto the retina starts at the first synapse, the cone pedicle, and each cone feeds its light signal into a minimum of eight different bipolar cell types. Hence, the morphological classification of bipolar cells is a prerequisite for analyzing retinal circuitry. Here we applied common bipolar cell markers to the cone-dominated ground squirrel retina, studied the labeling by confocal microscopy and electron microscopy, and compared the resulting bipolar cell types with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 75 publications
3
54
0
Order By: Relevance
“…Most of the diffuse bipolar cells in the primate retina are biased against S-cone contacts (Lee and Grünert, 2007), and, interestingly, the putative homologs of the DB1 bipolar in mouse (type-1, Ghosh et al, 2004) and ground squirrel (cb1 or former b7, Puller et al, 2011) are most likely M-cone selective (Breuninger et al, 2011; Li and DeVries, 2006). To determine the amount of S-cone input for DB1 cells, we double-labeled vertical sections and wholemounts with antibodies against SCGN and S-opsin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the diffuse bipolar cells in the primate retina are biased against S-cone contacts (Lee and Grünert, 2007), and, interestingly, the putative homologs of the DB1 bipolar in mouse (type-1, Ghosh et al, 2004) and ground squirrel (cb1 or former b7, Puller et al, 2011) are most likely M-cone selective (Breuninger et al, 2011; Li and DeVries, 2006). To determine the amount of S-cone input for DB1 cells, we double-labeled vertical sections and wholemounts with antibodies against SCGN and S-opsin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that NKCC is expressed in dendritic tips of ON bipolar cells, where it elicits an excitatory effect of GABA due to chloride accumulation [38], [40][42]. Furthermore, it is well-known that the blue cone bipolar cell is the major postsynaptic ON bipolar cell type of S-cones in various species including primate [54], [76], [87][89]. In summary, our findings suggest that there is a possibility of GABA release via HII horizontal cells beneath S-cones.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against S-opsin were used to label the corresponding cones including their pedicles in macaque and ground squirrel [69], [75], [76]. The specificity of the antibody was tested by the manufacturer with a Western blot analysis using mouse retinal extract, revealing a single band at the predicted size of 40 kDa.…”
Section: Methodsmentioning
confidence: 99%
“…Goat polyclonal antibodies directed at the N-terminal peptide of human blue-sensitive opsin (Santa Cruz, sc-14363, dilution 1:100) used to label the corresponding cones including their pedicles in primates as well as other species [43, 44]. The specificity of the antibody was tested by the manufacturer with a Western blot analysis using mouse retinal extract, revealing a single band at the predicted size of 40 kDa.…”
Section: Methodsmentioning
confidence: 99%